Failure pattern of elective nodal irradiation for esophageal squamous cell cancer treated with neoadjuvant chemoradiotherapy. (20th July 2018) - Zhou, Sha; Zhang, Li; Luo, Liling; Li, Qiaoqiao; Shen, Jingxian; Feng, Zizhen; Feng, Yanfen; Yang, Hong; Liu, Mengzhong; Xi, Mian
Abstract : This study aimed to analyze failure pattern of elective nodal irradiation in patients with esophageal squamous cell carcinoma after neoadjuvant chemoradiotherapy. The results indicated satisfactory infield control with elective nodal irradiation. Abstract: Objective: To analyze the failure pattern and clinical efficacy of elective nodal irradiation in patients with esophageal squamous cell carcinoma who received neoadjuvant chemoradiotherapy. Methods: We retrospectively analyzed 173 esophageal squamous cell carcinoma patients who received neoadjuvant chemoradiotherapy including elective nodal irradiation from 2002 to 2015. Failure pattern, survival and recurrence sites were analyzed. For patients with regional recurrences, the recurrence sites were analyzed in relation to an imaginary field of involved field irradiation. Results: After a median follow-up of 55.5 months, 58 patients (33.5%) developed recurrences. Among 22 patients with regional recurrences, infield failure occurred in 19 patients (86.4%) and outfield failure occurred in 3 patients (13.6%), of whom only 1 patient had an outfield failure without synchronous distant metastasis. Compared with the involved field irradiation field, 6 patients' failure sites (27.3%) were located in the involved field irradiation field and 13 patients' failure sites (59.1%) were out of the involved field irradiation field but within the elective nodal irradiation field. Conclusions: Since only a minority of patients had outfield regional recurrences, neoadjuvant chemoradiotherapy with elective nodal irradiation yields satisfactory infield control. More than half of the regional recurrences occurred within the elective nodal irradiation field but out of the involved field irradiation field. Prospective evaluation of whether elective nodal irradiation could lead to an improved survival outcome is necessary.